"Not Revenged, nor Repented of": Martyrs and England's Long Reformation. Issue 2 (3rd July 2019) - Gunther, Karl
ABSTRACT: This essay examines late sixteenth- and seventeenth-century English Protestants – primarily puritans – who believed that England had failed to satisfactorily avenge and repent for the deaths of the Marian martyrs. This failure, they argued, threatened imminent divine judgement and had also perhaps hindered the completion of the reformation that the martyrs had championed. After tracing the contours of these arguments, the essay focuses especially on the 1640s. It examines the remedies for Marian bloodguilt that were proposed by leading puritan divines and subsequently enacted by Parliament, as well as the debate that this notion engendered in the polarized environment of the English Civil War. Overall, the essay sheds new light on both the importance of martyrs in early modern England and on one of the ways in which contemporaries perceived and experienced England's long reformation.